(untitled) (Journal of Environmental Science and Natural Resources, 2017)
This study was carried out on estimation of inedible part (waste) of fruit and screening for potential pectin content (calcium pectate) in fruit wastes with respect to type, location and maturity. Fruit waste generation was significantly different in different fruit type, variety and maturity. In a whole fruit, amount of fruit waste (peel & core) was significantly higher than amount of fruit pulp. Among the waste evaluated the overall calcium pectate producing potential in order of merit were lemon, dragon fruit, guava, mango, jackfruit, banana, pomegranate, papaya, watermelon and pineapple. Unused fruit waste could be potential sources of pectin production. J. Environ. Sci. & Natural Resources, 10(1): 65-70 2017